Women show enhanced proprioceptive target estimation through visual-proprioceptive conflict resolution - de Melo, Anderson Barcelos; Landeira-Fernandez, Jesus; Krahe, Thomas Eichenberg (Frontiers in Psychology, 2024)
To form a unified and coherent perception of the organism's state and its relationship with the surrounding environment, the nervous system combines information from various sensory modalities through multisensory integration processes. Occasionally, data from two or more sensory channels may provide conflicting information. This is particularly evident in experiments using the mirrorguided drawing task and the mirror-box illusion, where there is conflict between positional estimates guided by vision and proprioception. This study combined two experimental protocols (the mirrorbox and the mirror-guided drawing tasks) to examine whether the learned resolution of visuoproprioceptive conflicts in the mirror-guided drawing task would improve proprioceptive target estimation of men and women during the mirror-box test. Our results confirm previous findings of visual reaching bias produced by the mirror-box illusion and show that this effect is progressively reduced by improvement in the mirror drawing task performance. However, this was only observed in women. We discuss these findings in the context of possible gender differences in multisensory integration processes as well as in embodiment.